Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Round Robin Terhadap Pemahaman Konsep Matematis Siswa Kelas VIII SMPN 5 Padang - Sari, Suci Mistika; Rahmi, Rahmi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
This research is motivated by the students lack of motivation to learn that lead to an understanding of mathematical concepts eighth grade students is still low test scores and results from the 1st half of eighth grade math students SMPN 5 Padang academic year 2012/2013. The research aimed to determine whether students understanding of mathematical concepts by using cooperative learning model Round Robin is better than the students understanding of mathematical concepts using conventional teaching class VIII SMPN5 Padang and to determine whether the implementation of cooperative learning model Round Robin can increase students motivation. This type of research is experimental research, the design of randomized trials on the subject. The research instrument was the final test in the form of essay with a reliability test is , and the students learning motivation questionnaire. Hypothesis testing using the t test with the help of the parties MINITAB, obtained P-value of 0.002 is less than Î± of 0.05, the research hypothesis is accepted. It can be concluded that the students understanding of mathematical concepts by using cooperative learning model Round Robin is better than the students understanding of mathematical concepts by using conventional learning class VIII SMPN5 Padang. Questionnaire analysis results indicate that the learning model Round Robin can increase students motivation.